CO observations of the molecular gas in the Galactic H ii region Sh2-48: Evidence for cloud–cloud collision as a trigger of high-mass star formation. (31st October 2018) - Torii, Kazufumi; Hattori, Yusuke; Matsuo, Mitsuhiro; Fujita, Shinji; Nishimura, Atsushi; Kohno, Mikito; Kuriki, Mika; Tsuda, Yuya; Minamidani, Tetsuhiro; Umemoto, Tomofumi; Kuno, Nario; Yoshiike, Satoshi; et al.
Abstract: Sh2-48 is a Galactic H ii region, 3.8 kpc distant, with an O9.5-type star identified at its center. As a part of the FOREST Unbiased Galactic plane Imaging survey using the Nobeyama 45 m telescope (FUGIN) project, we obtained a CO J = 1–0 data set for a large area of Sh2-48 at a spatial resolution of 21″ (∼0.4 pc), and used it to find a molecular cloud with a total molecular mass of ∼3.8 × 10 4 M ⊙ associated with Sh2-48. The molecular cloud has a systematic velocity shift in a velocity range of ∼42–47 km s −1 . On the lower-velocity side the CO emission spatially corresponds to the bright 8 μm filament at the western rim of Sh2-48; however, the CO emission with higher velocities separates into the eastern and western sides of the 8 μm filament. This velocity variation forms a V-shaped feature in the east–west direction on the position–velocity diagram. We found that these lower- and higher-velocity components are, unlike the infrared and radio-continuum data, physically associated with Sh2-48. To interpret the observed V-shaped velocity distribution, we assess a cloud–cloud collision scenario, and found, from a comparison between observations and simulations, that the velocity distribution is an expected outcome of a collision between a cylindrical cloud corresponding to the lower-velocity component and a spherical cloud, and that the two separate higher-velocity components are interpretable as collision-broken remnants of the spherical cloud. Based on the consistency between an estimated formation timescale of the H ii region, ∼1.3 Myr, and a timescale of the collision, we conclude that the high-mass star formation in Sh2-48 was triggered by the collision.